Improving Taxpayer Understanding in the UIN Salatiga Community Through e-SPT Filing Assistance Program - Pertiwi, Imanda Firmantyas Putri; Rahman, Taufikur (Profesional Muda Cendekia Publishing, 2024)
Research Aims: The general goal of this community service research is to provide assistance in filling out e-SPT for the academic community and surrounding residents of UIN Salatiga, analyze the effectiveness of the assistance program, and analyze the constructs of the TAM theory, which includes perceived usefulness, perceived ease of use, technology perception, and intention to use e-SPT. Design/methodology/approach: This research uses a combination of experimental-quantitative methods with primary data. The experimental method is conducted by comparing the participants' answers to tax-related questions and the technical aspects of filling out SPT before and after the assistance program. The quantitative method with primary data is applied by analyzing the participants' perception questionnaires regarding the usefulness, ease of use, perception of e-SPT technology, and intention to use e-SPT, both before and after the assistance program. The experimental method in this study will use a 2x2 between-subject factorial design. A saturated sample will be used in this research, with a total of 49 participants, comprising members of the academic community and the surrounding residents of UIN Salatiga. Research Findings: The socialization and assistance activities for filling out e-SPT proved to be effective, able to increase respondents' positive perceptions of the usefulness and ease of e-SPT, and were able to enhance the academic community's interest in using e-SPT as a tax reporting platform. However, the perception of usefulness did not influence the academic community's interest in using e-SPT, while the perception of ease of use and technological attitude were able to influence the interest in using e-SPT among the academic community of UIN Salatiga. Theoretical Contribution/Originality: This study provides both practical and theoretical contributions. Practically, it is expected that the assistance in filling out e-SPT will increase the understanding of the academic community and the surrounding residents of UIN Salatiga regarding taxation in general and the technical aspects of filling out e-SPT in particular. Theoretically, this study can contribute additional literature in the field of community service and taxation.